Menopause-Associated Comorbidities and Their Impact on COVID-19 Severity - Esseffar Sara; Bellahcen Said; Azizi Ghizlane; Ngadi Hamza; Moumen Abdelmajid (E3S Web of Conferences)
The Covid-19 pandemic has highlighted the role of biological factors, such as age, sex, and comorbidities, in determining disease severity. Menopause-related changes, including estrogen decline, may increase the severity of symptoms in women, particularly with comorbidities like cardiovascular diseases, hypertension, diabetes, and obesity. This study aims to explore the relationship between the severity of Covid-19 symptoms and menopause-related comorbidities and assess their impact on symptom intensity and recovery duration in menopausal women. A retrospective study was conducted with 50 menopausal women in Nador, Morocco, who had contracted Covid-19. Data were collected through structured interviews and analyzed using SPSS software. Associations between comorbidities and symptom severity were assessed using Chi-Square tests, and recovery times were compared using t-tests. Cardiovascular diseases, diabetes, and high blood pressure were significantly associated with more intense Covid-19 symptoms. Menopausal women with cardiovascular diseases had longer recovery times compared to those without. Obesity showed borderline significance for symptom intensity and recovery time. Comorbidities like cardiovascular disease and diabetes are linked to more severe Covid-19 symptoms and prolonged recovery times in menopausal women. These findings underline the importance of managing comorbid conditions in this population to improve health outcomes.